2009
DOI: 10.1007/s00223-009-9308-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Prolonged Submersion on Bone Strength and Metabolism in Young Healthy Submariners

Abstract: Submariners taking part in prolonged missions are exposed to environmental factors that may adversely affect bone health. Among these, relatively high levels of CO(2), lack of sunlight exposure affecting vitamin D metabolism, limited physical activity, and altered dietary habits. The aims of this study were to examine the effect of a prolonged submersion (30 days) on changes in bone strength using quantitative bone speed of sound and in markers of bone metabolism that include bone turnover (BAP, PINP, TRAP5b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 24 publications
3
42
2
Order By: Relevance
“…Confinement studies have to date examined psychosocial [1], biomedical [2], skilled motor [2], [3] and immune system [4] variables. Aside from the most common case of prolonged confinement, imprisonment, individuals are also confined as part of over-wintering in isolated regions of the Earth [5], military operations [3], [6] and ground based spaceflight operation simulation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Confinement studies have to date examined psychosocial [1], biomedical [2], skilled motor [2], [3] and immune system [4] variables. Aside from the most common case of prolonged confinement, imprisonment, individuals are also confined as part of over-wintering in isolated regions of the Earth [5], military operations [3], [6] and ground based spaceflight operation simulation [1].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Schlichting et al ( 77 ) also reported a decrease in 25-(OH) vitamin D levels over a 2-mo deployment. Moreover, a recent study of Israeli submariners found that a 30-d submersion led to decreased bone density and 25-(OH) levels, but it also led to decreased circulating parathyroid hormone levels and bone remodeling markers, along with increased circulating calcium levels ( 44 ). Taken together, these data suggest that deployments of ; 2 mo result in bone resorption, but deployments of 1 mo may only result in reduced bone metabolism.…”
Section: Ways To Mitigate the Potential For Hypercortisolism And Its mentioning
confidence: 85%
“…These studies demonstrated that bone change starts with the non-weighted bearing period and can be detected 4–6 weeks after the immobilization period (the entity is different according to individual parameters). In a study carried out using a cohort of patients with ankle fractures the peak of the bone loss was around 4 months; the timing for the peak has been discussed in the literature [2; 3; 5; 7; 11; 18], ranging between 4 to 10 weeks. The original bone mass will not be achieved for many years and the architecture of the bone will never been restored, resulting in weaker bone than normal [25] that is easier to break [26].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, 20 subregions were identified and graded as shown in Table 2 for the following morphological criteria as seen on fluid sensitive fat-saturated images: (i) bone marrow signal abnormality (none, subtle—10% of subregion, mild—10–40% of subregion, moderate—> 40% of subregion or severe-> 75% of subregion); (ii) signal intensity relative to hyaline cartilage (hypointense, isointense, hyperintense); (iii) morphology of signal alteration (no present, dotted, linear, patchy or confluent); (iv) presence or absence of hypervascularity [2, 9, 16], qualitatively defined as increased serpiginous linear vascular structures in the periphery of the bone [2, 9]; (v) presence of alteration on T1-weighted images recorded as present or absent. Fig.…”
Section: Methodsmentioning
confidence: 99%